The Effect of Concussion on Head Stabilization and Body Movement Strategies in Youth Performing a Dual-Task - Legace, Elizabeth (Université d'Ottawa / University of Ottawa, 2018)
According to the Guidelines for Diagnosing and Managing Pediatric Concussion, concussion is defined as “an injury to the brain caused by a blow to the head or to another part of the body that causes the head to spin or jolt” (Zemek, Duval, Dematteo, 2014, p. 40), and is a common injury among the youth population (National Institute of Health, 1999). When moving or remaining stationary the head can be stabilized in two ways: head stabilized in space and head stabilized on trunk (Bazarian, Veazie, Mookerjee, & Lerner, 2006). When under anxiety inducing conditions during development and when learning novel tasks individuals tend to shift from a head stabilized in space strategy to a head stabilized on trunk strategy in an effort to decrease the degrees of freedom required to move the head (Assaiante, McKinley, & Amblard, 1997). However, it is unclear whether certain pathologies result in movement strategies and whether these are influenced by the difficulty of the task performed. Objective The present study examined the effects of concussion on head stabilization strategies in adolescents while performing three dual-tasks. Participants Fifty-four participants, 24 concussed with post- concussion syndrome (age, 13.5 ± 1.9 years; 15 females, 9 males) and 30 healthy typically developing adolescents (age, 14.3 ± 1.7 years; 12 females, 18 males), performed one session of three dual-task conditions. Centre of pressure along with head, trunk and pelvis kinematics were captured during task performance using a Nintendo® Wii Balance Board and Ascension 3D Guidance TrakSTAR respectively. A head anchoring index (AI) was used to identify either head stabilized in space or head stabilized on trunk movement strategies, while center of pressure was collected to further support the use of movement strategies. Results There were no significant differences in AI between the two groups in any of the three dual-task conditions. Conclusion These results could be attributed to balance recovery or lack of balance problems in the concussed population.
Keywords: Concussion; Balance